Holocene shifts of the southern westerlies across the South Atlantic. (16th February 2015) - Voigt, Ines; Chiessi, Cristiano M.; Prange, Matthias; Mulitza, Stefan; Groeneveld, Jeroen; Varma, Vidya; Henrich, Ruediger
Abstract: The southern westerly winds (SWW) exert a crucial influence over the world ocean and climate. Nevertheless, a comprehensive understanding of the Holocene temporal and spatial evolution of the SWW remains a significant challenge due to the sparsity of high‐resolution marine archives and appropriate SWW proxies. Here we present a north‐south transect of high‐resolution planktonic foraminiferal oxygen isotope records from the western South Atlantic. Our proxy records reveal Holocene migrations of the Brazil‐Malvinas Confluence (BMC), a highly sensitive feature for changes in the position and strength of the northern portion of the SWW. Through the tight coupling of the BMC position to the large‐scale wind field, the records allow a quantitative reconstruction of Holocene latitudinal displacements of the SWW across the South Atlantic. Our data reveal a gradual poleward movement of the SWW by about 1–1.5° from the early to the mid‐Holocene. Afterward, variability in the SWW is dominated by millennial scale displacements on the order of 1° in latitude with no recognizable longer‐term trend. These findings are confronted with results from a state‐of‐the‐art transient Holocene climate simulation using a comprehensive coupled atmosphere‐ocean general circulation model. Proxy‐inferred and modeled SWW shifts compare qualitatively, but the model underestimates both orbitally forced multimillennial and internal millennial SWW variability by almost an order of magnitude. The underestimated natural variability implies a substantial uncertainty in model projections of future SWW shifts. Key Points: Southern Westerly Winds, Brazil‐Malvinas Confluence, Holocene